Odor mental imagery in non-experts in odors: a paradox? - ROYET, Jean-Pierre; Delon-Martin, Chantal; Plailly, Jane (Frontiers in Human Neuroscience, 2013)
In agreement with the theoretical framework stipulating that mental images arise from neural activity in early sensory cortices, the primary olfactory cortex (i.e., the piriform cortex, PC) is activated when non-olfactory-experts try to generate odor mental images. This finding strongly contrasts with the allegation that it is typically impossible to mentally imagine odors. However, other neurophysiological or cognitive processes engaged in the endeavor of odor mental imagery such as sniffing, attention, expectation and cross-modal interactions involve the PC and could explain this paradox. To unambiguously study the odor mental imagery, we first argued the need to investigate odor experts who have learned to specifically reactivate olfactory percepts. We then assert the necessity to explore the network dedicated to this function by considering variations in both the activity level and the connection strength of the areas belonging to this network as a function of the level of expertise of the odor experts.